Sheikh Muhammad Ashraf Al-Azeem Al-Abady and his Method in ‘Awn Al-Mabood - الشيخ محمد أشرف العظيم الآبادي ومنهجه في كتابه "عون المعبود (USIM Press, 2024)
Journal of Hadith Studies Volume 8 No.1 Page (100-108)